Comparison of Geospatial Data Management between Indonesia’s One Data and One Map Policy - Risky Kurniawan; Teguh Kurniawan (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
Geospatial data is one of the important supports in spatial-based national development. However, there is a problem with the large amount of data overlap. One of the reasons for this data overlap is the difference in the references used. Therefore, a policy is needed regarding the implementation of geospatial data. The Indonesian government has enacted Peraturan Presiden (presidential regulations) of Indonesia’s One Data and One Map Policy. Those policies aim to produce sufficient data. Indonesia's One Data Policy regulates the management of statistical, geospatial, and state financial data at the national level. But, the One Map Policy only regulates the management of geospatial data. As two different policies with the same level, have similar names, and have intersect in the management of geospatial data, there is a potential for misunderstanding in implementing both policies. This article aims to identify the similarities and differences between the two policies. The method is a literature study from various sources. This article used analysis comparison. The findings identified similarities and differences with almost the same amount. Based on the similarities and differences, recommendations are made. The author proposes a synergy of geospatial data management mechanisms or considers deregulate one of the policies after the policy target is completed with further study.